Pengaruh Pertumbuhan Ekonomi dan Pendapatan Asli Daerah Terhadap Belanja Modal pada Kota Langsa Provinsi Aceh Periode 2012-2021 - Isharyanto Isharyanto; Jadmiko Anom Husodo; Sri Wahyuni; Maria Madalina; Sunny Ummul Firdaus (CV. Syntax Corporation Indonesia, 2022)
The Constitutional Court (MK) has read out Decision Number 91/PUU-XVIII/2020 regarding the submission of judicial review from several parties regarding Law Number 11 of 2020 concerning Job Creation (UU Cipta Kerja). The decision essentially states that the Job Creation Law is contrary to the 1945 Constitution of the Republic of Indonesia and does not have conditionally binding legal force as long as it does not mean that